The Influence Of Organizational Dna On The Quality Of Healthcare Services - An Empirical Study In The University Hospital Center Of Sidi-belabbas- - Moulai, Amina; Derdar, Hadjer (جامعة الوادي - University of Eloued, 2021)
The organizational DNA is one of the newly adopted metaphorical approaches in the field of business administration, which helps in diagnosing the organization's illnesses and proposing the right remedies. this study aimed to discuss the impact of organizational DNA elements on the SERVQUAL of healthcare. The study reached a set of results, the most important of which are: -There is a positive impact of the components of OrgDNA on the healthcare quality dimensions, where the greatest effect occurs on the reliability of services delivered, and the weak effect appears on the empathy of health services providers. -if the foundations of the organization suffer from problems, typically the quality of its services will not be satisfactory
مقال
Keywords: Organizational DNA ; SERVQUAL ; healthcare services ; structural equations